Understanding Data Videos: Looking at Narrative Visualization through the Cinematography Lens - Amini, Fereshteh; Henry Riche, Nathalie; Lee, Bongshin; Hurter, Christophe; Irani, Pourang (ACM, 2015)
Data videos, motion graphics that incorporate visualizations about facts, are increasingly gaining popularity as a means of telling stories with data. However, very little is systematically recorded about (a) what elements are featured in data videos and (b) the processes used to create them. In this article, we provide initial insights to build this knowledge. We first report on a qualitative analysis of 50 professionally designed data videos, extracting and exposing their most salient constituents. Second, we report on a series of workshops with experienced storytellers from cinematography, graphics design and screenplay writing. We provided them with a set of data facts and visualizations and observed them create storyboards for data videos. From these exploratory studies, we derive broader implications for the design of an authoring tool to enable a wide audience to create data videos. Our findings highlight the importance of providing a flexible tool supporting a non-linear creation process and allowing users to iteratively go back to different phases of the process.